Flipped classroom in financial accounting: analysis of student perception - Ciudad Gómez, Adelaida (Journal of Management and Business Education, 2024)
In Higher Education and in Financial Accounting, we have designed an educational innovation, within a comprehensive learning approach, through the use of the "flipped classroom" methodology, "blended learning", e-rubrics, collaborative learning and self-assessment / Peer evaluation, guiding us towards a formative and shared evaluation, being implemented in "Financial Accounting III" during the 2020-2021 and 2021-2022 academic years. The purpose of this work is, within a «Design-Based Research» strategy, to explore the perception and satisfaction of the student with the «flipped classroom» methodology and if it differs according to the student's gender, an experience in the classroom where they participated 67 students, with a non-probabilistic sample of 39 students who completed the questionnaire hosted on the Moodle platform, an instrument with a reliability level of α= .940 (Cronbach's Alpha). For the analysis and discussion of the results, measures of central position and dispersion have been used, together with the Mann Whitney U statistic, showing the results a positive perception of the students towards the adopted methodology, without significant differences depending on their gender, a finding that provides support to higher education financial accounting professors interested in using the flipped classroom.